If Sons, Then Heirs A Study of Kinship and Ethnicity in the Letters of Pual - Hodge, Caroline Johnson (Oxford Oxford University Press, 2007)
"If Sons, Then Heirs demonstrates that Paul's thinking is immersed in the story of Israel. He speaks not as a Christian theologian, but as a first-century Jewish teacher of gentiles responding to concrete situations in these early communities of Christ-fo
Keywords: Bible. -- Epistles of Paul -- Criticism, interpretation, etc. Kinship -- Biblical teaching. Ethnicity -- Biblical teaching